The Association of Preoperative Medication Administration and Preoperative and Intraoperative Factors With Postoperative Urinary Retention After Urogynecologic Surgery. Issue 9 (September 2021) - Schmidt, Payton; Kobernik, Emily K.; Fairchild, Pamela S.; Anderson, Alec; Lanham, Michael; Berger, Mitchell B.
Abstract : Objectives: The aim of this study was to determine if preoperative medication administration is associated with postoperative urinary retention (PUR) after urogynecologic procedures and identify preoperative and intraoperative factors that are predictive of PUR. Methods: A retrospective review of patients who underwent prolapse and/or incontinence surgery was performed. The primary outcome was PUR, defined as postoperative retrograde void trial with postvoid residuals of greater than 100 mL. Bivariate analysis was performed to compare demographics and preoperative and intraoperative characteristics of women with and without PUR, and multivariable logistic regression modeling was used to identify independent predictors of PUR. Results: Of women in this cohort, 44.8% (364/813) had PUR. There were no significant differences in preoperative medication administration in women with and without PUR. Age older than 60 years (adjusted odds ratio [aOR], 1.48; 95% confidence interval [CI], 1.09–2.02), combined prolapse and incontinence surgery (aOR, 1.84; 95% CI, 1.29–2.62), vaginal hysterectomy (aOR, 1.66; 95% CI, 1.66–2.38), and procedure time (aOR, 1.01; 95% CI, 1.00–1.01) were associated with increased odds of PUR, whereas laparoscopic sacrocolpopexy was associated with lower odds (aOR, 0.22; 95% CI, 0.10–0.46). Discussion: Although preoperative medication administration was not associated with PUR, other clinically important variables were age older than 60 years, vaginal hysterectomy, incontinence and prolapse surgery, or longer procedure time. Sacrocolpopexy reduced the odds of PUR by approximately 80%. These factors may be useful in preoperative and postoperative counseling regarding PUR after urogynecologic surgery.